The Correlation between Students’ Mastery of Simple Past Tense and Their Ability in Translating Recount Text at the First Year of SMA Muhammadiyah Rambah - Retno Sutrayani; Qonaah Nuryan Arif; Esti Raihana (Lembaga Pengembangan Kinerja Dosen, 2025)
This research investigates the correlation between students’ mastery of simple past tense and their ability in translating recount texts at the first year of SMA Muhammadiyah Rambah. The research was motivated by the fact that many students struggle to use past verb forms, particularly irregular verbs, which are essential in recount texts. Translation is not only about word substitution but also requires grammatical accuracy, especially in understanding tenses. This research employed a quantitative approach with a correlational design. The population consisted of 29 tenth-grade students, who were also used as the total sample. Data were collected using two instruments there are a 25-item multiple-choice test to measure students’ mastery of the simple past tense, and a translation essay of a recount text to evaluate their translation ability. The data were analyzed using Pearson’s product-moment correlation after passing validity, reliability, normality, and linearity tests. The findings showed a significant and very strong positive correlation between the two variables, with a correlation coefficient of 0.868 and a significance value of 0.000 < 0.05. This result indicates that students with better mastery of the simple past tense tend to achieve higher performance in translating recount texts. The findings also suggest that grammar, particularly tense mastery, is best learned when combined with practical activities such as translation rather than being taught in isolation. Teachers are encouraged to design learning strategies that integrate tense instruction with translation practice to strengthen students’ grammatical and translation abilities.